Perlindungan Hukum Bagi Pemenang Lelang Apabila Obyek Lelang Disita Dalam Perkara Pidana - Desminurva Festia Amalia (Universitas Muhammadiyah Jember, 2019)
Auction as a sale-purchase agreement, so the regulation by BW also valid in an auction. Elements of auction are same in definition of sale-purchase, there are, the subject law as seller and buyer, the agreement between seller and buyer about goods and price, the rights and obligations which arising of parties the seller and buyer. The essence of auction and trading is the goods and the payment of price. Auction is trading contracts, the legal relation in auction is between the seller, bidder buyers through official auction.In its implementation, sometimes there are still many problems happened, one of them is when goods were auctioned off, especially an executed guarantee and put civil seized, turns out that caught with criminal issue faced by the owner, while bidding has been implemented and has been choosen a winner of auction to have paid the price. Especially if it to do execution/seized. Even in article 39 paragraph (2) KUHAP said that civil execution of the goods can also criminal execution. So the thesis aims to understand legal certainty of the auction and what kind of legal efforts that can do by the auctions winner who feel lose out if objects auction seized in criminal cases.